2018
DOI: 10.1021/acs.energyfuels.8b02374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geographical Location on the Variation in Products Formed from the Hydrothermal Liquefaction of Ulva intestinalis

Abstract: Hydrothermal liquefaction (HTL) of macroalgae offers a promising route to advanced biofuel production, although the distinct biochemical compositions of different macroalgae species can lead to widely different product yields and compositions. On the basis of this, there is an implicit assumption that there exists a universal optimal feedstock species for a bioenergy-based biorefinery, which could be exploited across a wide region. However, no studies to date have examined the effect of this large geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The samples were initially identified morphologically and were assessed as a feedstock for hydrothermal liquefaction (Raikova et al, 2020). However, recent studies have identified strong morphological plasticity within Ulva spp., as well as the occurrence of cryptic species within the genus (Steinhagen, Karez, & Weinberger, 2019).…”
Section: Species Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were initially identified morphologically and were assessed as a feedstock for hydrothermal liquefaction (Raikova et al, 2020). However, recent studies have identified strong morphological plasticity within Ulva spp., as well as the occurrence of cryptic species within the genus (Steinhagen, Karez, & Weinberger, 2019).…”
Section: Species Identificationmentioning
confidence: 99%
“…Protein content was determined by analysing the nitrogen content on an elemental analyser (Carlo Erba Flash 2000 elemental analyser, at London Metropolitan University) and the nitrogen was converted to protein by a conversion factor of 4.73 (Biancarosa et al, 2017). Metals and some non-metal elements were analysed by inductively coupled plasma optical emission spectrometry (ICP-OES) after digestion in aqua regia as described (Raikova et al, 2020). ICP-OES was carried out externally by Yara UK Ltd using an Agilent 700 series inductively coupled plasma optical emission spectrometer.…”
Section: Analyses Of Biomass Componentsmentioning
confidence: 99%
“…Seasonal variations in growth and composition of Laminaria digitata and the implications for thermochemical and biochemical biofuel production routes were mapped by Adams et al 14,15 Their results show large variations in chemical composition throughout the year with July giving the best yields for such different processes as pyrolysis and fermentation to ethanol. Raikova et al 16 analysed the effect of geographical location on biocrude yields from macroalgae HTL, stating that significant variations in composition were observed between different regions (Baltic and Atlantic), but even between sites with close proximity. Localized conditions are considered to affect HTL product composition significantly.…”
Section: State Of the Artmentioning
confidence: 99%
“…Thus far, the most well researched macroalgae species have been from the genera Enteromorpha ( Ulva ) and Laminaria . Anastasakis and Ross described the HTL of three Laminaria types, as well as the brown macroalgae, Alaria esculenta , collected off the coast of Scotland, obtaining the highest yields of 13% bio‐crude for L. digitata and A. esculenta .…”
Section: Hydrothermal Liquefactionmentioning
confidence: 99%
“…The compositions of the resulting bio‐crudes also displayed differences – H/C ratio varied from 1.04–1.28, and bio‐crude nitrogen ranged between 3.0–4.9%. A more recent study of geographical variation demonstrated that there is even a high degree of variability between bio‐crude yields from the same species of macroalgae collected at the same time from sites within relatively close proximity (on the km scale) …”
Section: Hydrothermal Liquefactionmentioning
confidence: 99%